Pro-poor intervention strategies in irrigated agriculture in Asia: poverty in irrigated agriculture: issues and options: Vietnam - Doan Doan Tuan; Biltonen, Eric; Hussain, Intizar; Nguyen Van Quy; Dang The Phong; Le Ngoc Hung; Dinh The Hung; Nguyen Xuan Tiep; Pham van Ban; Lam Quang Dung; Nguyen Danh Minh; Le Van Chinh; et al. (International Water Management Institute, 2004)
IWMI-ADB Project